Effectiveness of wetland plants as biofilters for inhalable particles in an urban park. (1st September 2018) - Yan, Guoxin; Liu, Jiakai; Zhu, Lijuan; Zhai, Jiexiu; Cong, Ling; Ma, Wenmei; Wang, Yu; Wu, Yanan; Zhang, Zhenming
Abstract: Forests and vegetation are known to play an important role in capturing air pollutants, whereas the role of wetland plants in this context has been poorly understood. This study focused on particle accumulation in six common wetland plant species in a wetland in Beijing, China. The aim of the study was to show the capacity of the six plants species to accumulate particulates of two different size fractions (fine particles: diameter < 2.5 μm; coarse particles: diameter ranging from 2.5 to 10 μm) over three growing seasons. This study also discussed the differences among species with respect to their ability to accumulate particles and their unique microstructures and investigated the possible associations between stoma density, stoma width, stoma length, groove width, and particle accumulation. The results showed that Phragmites australis accumulated a considerable proportion of both coarse and fine particles. The leaf surface microstructure was observed using scanning electron microscopy (SEM). Microstructures, such as trichomes, were good at capturing particles, but there was no relationship between surface roughness and particle accumulation. Regression analysis showed that the correlation between stoma density, groove width, stoma width, and particle accumulation was moderate (R 2 = 0.45, 0.30, and 0.34, respectively). Thus, wetlands in urban areas could provide an important ecosystem service: accumulation of hazardous particulate matter. The results of this study could be useful to select wetland species with a strong particle-accumulating ability. P. australis has the potential to be a good biofilter in artificial wetlands in cities. In addition, when selecting species, it is better to select those with more trichomes or hairs on their leaf surfaces.